ANALISIS YURIDIS PUTUSAN ULTRA PETITA TERHADAP PELAKU TINDAK PIDANA NARKOTIKA BERDASARKAN KUHAP - Chelsy Tamara Siahaan; Abdul Ficar Hadjar (Reformasi Hukum Trisakti, 2023)
A judge's ruling is a part of the criminal justice system. Because the indictment serves as the foundation for assessing criminal cases, the judge's decision must be based on it. In actuality, judgments are frequently made without regard to indictments. What is the legal foundation for and ramifications of the ultra petita decision? The research methodology employs normative law, is descriptive analytical, relies on secondary data, uses qualitative data analysis, and draws findings using a deductive approach. The findings of the study and debate demonstrate that the cassation decision was erroneous since the judge did not base his decision on the public prosecutor's indictment, whereas the defendant was charged with using Article 112 paragraph (1) in conjunction with Article 132 paragraph (1) letter a of Law no. 35 of 2009 concerning Narcotics. However, in the decision at the cassation level, the panel of judges decided to use Article 127 paragraph (1) letter a of Law No. 35 of 2009 concerning Narcotics in which the Public Prosecutor did not indict that article. Decisions that exceed charges or ultra petita are prohibited and regulated in Article 182 paragraphs (3) and (4) in conjunction with Article 197 paragraph (1) of the Criminal Procedure Code. Conclusion; then the ultra petita decision is prohibited and regulated in Article 182 paragraphs (3) and (4) in conjunction with Article 197 paragraph (1) of the Criminal Procedure Code.